2012
DOI: 10.1002/jat.2796
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy analysis and mapping the biodistribution of inhaled carbon nanotubes in the lungs and blood of mice

Abstract: Because of their small size, robust structure, and unique characteristics, carbon nanotubes (CNTs) are increasingly used in a variety of biomedical applications, materials, and products. As their use increases, so does the likelihood of unintended release and human exposure. Therefore, it is important to establish their potential biodistribution and biopersistence to better understand the potential effects of their exposure to humans. This study examines distribution of CNTs in CD-1 mice following exposure by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 64 publications
(90 reference statements)
1
23
0
1
Order By: Relevance
“…1 and 3-8 that Raman spectra of investigated biosamples and recorded by 632.8 nm laser excitation exhibit low S/N ratio. Since a similar Raman spectra of blood and lung were recorded by Ingle and coworkers [27] by using a different Raman instrumentation, a primary reason for this observation is probably a low quantum efficiency of the detector and grating that are usually optimized for the 488 and 532 nm excitations. Thus, a good quality 633 nm Raman bio-spectrum is recorded when Raman scattering is Raw spectra of the liver tissue from three animals (blue, red and green spectra for each animal) recorded using a 532 nm laser excitation that demonstrate the intra-and inter-sample variability.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…1 and 3-8 that Raman spectra of investigated biosamples and recorded by 632.8 nm laser excitation exhibit low S/N ratio. Since a similar Raman spectra of blood and lung were recorded by Ingle and coworkers [27] by using a different Raman instrumentation, a primary reason for this observation is probably a low quantum efficiency of the detector and grating that are usually optimized for the 488 and 532 nm excitations. Thus, a good quality 633 nm Raman bio-spectrum is recorded when Raman scattering is Raw spectra of the liver tissue from three animals (blue, red and green spectra for each animal) recorded using a 532 nm laser excitation that demonstrate the intra-and inter-sample variability.…”
Section: Resultsmentioning
confidence: 96%
“…1 and 4). This problem was also noticed in Raman studies on unfixed (air-dried) cross sections of lung tissues collected by using these laser lines [26,27]. Despite this fact bands present in all spectra provide some information about lipids and proteins.…”
Section: Spectral Features Of Lung Tissuementioning
confidence: 84%
See 1 more Smart Citation
“…For instance, nanotubes can be used for cancer detection. Ingle et al used functionalized single-walled carbon nanotubes (SWCNT) in the form of an aerosol in the lungs of mice to detect lung cancer [59]. Analysis showed that after the arrival of the aerosol to the lungs of mice, blood samples can be used for the detection based on SERS.…”
Section: Nanoparticles and Raman Techniquesmentioning
confidence: 99%
“…(2013) [20] podają, że u myszy inhalowanych aerozolem SWCNT (średnica włókien 0,8-2,4 nm) zaobserwowano translokację nanorurek węglowych do układu krążenia. Zwierzęta inhalowano przez 15 min i badano po 24 godz.…”
Section: Toksykokinetykaunclassified